Capacidad de producción económico-agrícola de dos áreas del Cantón de Turrialba, Costa Rica - Rodriguez, Panfilo; Peterson, Arthur W. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Studies in the United States, Canada, China and the Caribbean region have shown that between broad agricultural regions within the same country it is usual for differences in the productive capacity of land to be reflected in variations in the amount of land per person rather than in the production per person. Within agricultural regions having similar climatic and marketing characteristics, however, differences in the productive capacity of land usually are not associated with a compensating change in the area of land in farms per person but rather with differences in production per person. In order to test this latter relationship under Central American conditions, two areas of land near the town of Turrialba, Costa Rica were chosen for study These two areas are situated in the same climatic and marketing zones (same agricultural region) but differ in productive capacity per unit of area. Through the use of data from the 1948 trial census for the Turrialba Cantón calculations were made showing population, land use, total production, area of land per person and prodm tion per person The following data summarize the most important findings.